Severity of Emotional Maladaptation and Ability to Recognize Emotions in Patients with Facial Nerve Damage - A.A. Rakhmanina; A.B. Kholmogorova; L.B. Zavaliy (Экспериментальная психология)
According to the facial feedback hypothesis, disruption of the afferent connection from the facial muscles, which is a consequence of facial nerve damage, can reduce the emotional response or decrease its intensity, which is also confirmed by studies of patients who received botulinum toxin injections. The results of studies of emotion recognition in patients with facial nerve damage are contradictory and do not take into account other factors that may affect the recognition process. The aim of this study is to identify the features of emotion recognition by faces and the severity of emotional maladaptation symptoms in patients with facial nerve impairment. The study sample consisted of a control group of healthy respondents (N = 37) and a main group - 30 patients with facial nerve damage (neuropathy, hemifacial spasm, 80% of them with severity of damage of III-VI degree). To assess the severity of emotional maladjustment, the following scales were used: A. Leary's Fear of Negative Evaluation, A. Beck's Depression, and Situational Dissatisfaction with One's Appearance (SIBID); to assess the ability to understand and recognize emotions, the Alexithymia Scale (TAS-20) and N.S. Kurek's Method of Recognizing Emotions by Facial Expressions were used. Compared with the control group, patients with facial nerve damage had higher rates of alexithymia and were also worse at recognizing high intensity contempt. Compared with the control group, they had significantly higher rates of social anxiety (fear of negative evaluation) and depression. The obtained results allow us to draw preliminary conclusions that patients with facial nerve damage have a reduced ability to recognize emotions, which may be associated with both a disruption of efferent connections from the facial nerve and symptoms of emotional maladaptation.